2018
DOI: 10.1002/jcb.27135
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin inhibits mast cell–mediated allergic inflammation in allergic rhinitis

Abstract: Paeoniflorin (PF), one of the main effective ingredients from the root of Paeonia lactiflora Pall., was reported to possess antitumor, anti-inflammatory, and antiallergic properties. However, the roles of PF in activated human mast cell line, HMC-1 cells, have not yet been elucidated. Thus, the aim of this study was to examine the antiallergic and anti-inflammatory effects of PF on phorbol-12-myristate 13-acetate plus calcium ionophore (PMACI)-induced human mast cells and to identify the mechanism responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…12 It can aggravate damage of nasal mucosa by degranulation and release large numbers of inflammatory transmitters. Many inflammation factors are involved in the progression of AR, although the mechanisms remain unclear 13 , 14 Our results indicated that polymorphisms of the VDR gene Fok I locus are associated with AR, and the A allele of FokI/rs22285570 increases the risk for AR; The Fok I/rs22285570 polymorphism also affects serum levels VDR mRNA. The IL-6, IL-8, and IL-10 levels were elevated in the AR group, indicating that inflammation plays an important in the pathophysiology of AR.…”
Section: Discussionmentioning
confidence: 71%
“…12 It can aggravate damage of nasal mucosa by degranulation and release large numbers of inflammatory transmitters. Many inflammation factors are involved in the progression of AR, although the mechanisms remain unclear 13 , 14 Our results indicated that polymorphisms of the VDR gene Fok I locus are associated with AR, and the A allele of FokI/rs22285570 increases the risk for AR; The Fok I/rs22285570 polymorphism also affects serum levels VDR mRNA. The IL-6, IL-8, and IL-10 levels were elevated in the AR group, indicating that inflammation plays an important in the pathophysiology of AR.…”
Section: Discussionmentioning
confidence: 71%
“…As a monoterpene glycoside, paeoniflorin is the main active ingredient in the roots of Chinese traditional Chinese medicine paeoniflorin [10]. Numerous pharmacological experiments have proved that paeoniflorin has significant anti-inflammatory, immunomodulatory, analgesic, anticoagulant, and antioxidant effects [11,12]. However, the mechanism of paeoniflorin in MIRI is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…84 Another agent with the potential for inhibiting both FcεRI and MRFPRX2 signaling in mast cells is paeoniflorin, a bioactive component in peony flower extracts; the mast cell stabilizing action of this agent has been demonstrated both in mast cell cultures and in rodent allergy models. [85][86][87][88] The direct molecular target of its action in this regard has yet to be defined.…”
Section: Discussion On Nutraceutical Strategies For Mast Cell Stabilizationmentioning
confidence: 99%